Exploring the Beauty of Islamic Values Through Metaphorical Expressions in Literary Work - Ferdinal, Ferdinal; Oktavianus, Oktavianus; Zahid, Indirawati (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Islamic values are strongly tied to Muslims’ ability to live in this world and the Hereafter. As a result, continuous research on Islamic ideals is required. These ideals can serve as a guideline for Muslims in their daily lives. In this regard, this research investigates Islamic principles reflected through metaphorical expressions in a literary work. This research employs a qualitative approach, an in-depth examination of a phenomenon. This study’s data was derived from metaphorical language containing Islamic ideals. The source of the data is Hamka’s novel Di Bawah Lindungan Ka’bah. The Qur’an and Hadith are utilized to analyze Islamic principles, while metaphor theory is employed to study metaphorical terms. The study’s findings indicate that this novel has the core values for hablun min Allah and hablun min al-nas. The value of hablun min Allah is firm faith (‘aqidah) in Allah. Hablun min al-nas’s main principles include the pursuit of trustworthiness, togetherness, affection, kindness, carefulness, and politeness, all leading to prosperity. In expressing and preaching Islamic ideals, metaphorical terms serve as a medium to describe a situation, underline a message, deliver values politely, and create aesthetic and artistic effects.